1999
DOI: 10.1103/physreve.60.5175
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evidence for divergent Burnett coefficients

Abstract: In previous papers [Phys. Rev. A 41, 4501 (1990); Phys. Rev. E 18, 3178 (1993)], simple equilibrium expressions were obtained for nonlinear Burnett coefficients. A preliminary calculation of a 32-particle Lennard-Jones fluid was presented in the previous papers. Now, sufficient resources have become available to address the question of whether nonlinear Burnett coefficients are finite for soft spheres. The hard sphere case is known to have infinite nonlinear Burnett coefficients (i.e., a nonanalytic constituti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, notice should be made about the results from molecular dynamics for shock waves in dense fluids and in particular to the work done recently [173] that apparently exhibits a contradiction with Fourier's Law. Furthermore, for dense fluids evidence for divergent Burnett coefficients has been provided [174,175]. 17 For the dilute gas 17 In our opinion the goal is to have a theory that can be applied to different situations.…”
Section: Shock Wavesmentioning
confidence: 98%
“…However, notice should be made about the results from molecular dynamics for shock waves in dense fluids and in particular to the work done recently [173] that apparently exhibits a contradiction with Fourier's Law. Furthermore, for dense fluids evidence for divergent Burnett coefficients has been provided [174,175]. 17 For the dilute gas 17 In our opinion the goal is to have a theory that can be applied to different situations.…”
Section: Shock Wavesmentioning
confidence: 98%
“…Here κ NL is a kinetic coefficient commonly referred to as a nonlinear Burnett coefficient [33,34]. As has been discussed elsewhere [35][36][37][38], it is well known that κ NL diverges linearly in the large system size, L, due to longtime-tails effects. To take this divergence into account we wrote in our previous publications [29,30]…”
Section: Introductionmentioning
confidence: 95%
“…Worse still, it is well-known that the higher-order corrections in the gradient expansion to the Navier-Stokes equations are ill-posed and many questions about the meaningfulness of the Chapman-Enskog solutions to the Boltzmann equations have been raised (Cercignani 1975;Ernst et al 1978). Mode-coupling theories (Ernst & Dorfman 1975;Ernst et al 1978) and computer simulations (Standish 1999) have revealed that the transport coefficients corresponding to the Burnett and super-Burnett terms actually diverge in the thermodynamic limit, indicating non-analytic (in the gradients) corrections.…”
Section: Introductionmentioning
confidence: 99%